Development of African freight transport: The case of Kenya - Patrick O. Alila; Meleckidzedeck Khayesi; Walter Odhiambo; Poul Ove Pedersen (Danish Institute for International Studies (DIIS), 2005)
The Kenyan transport system is still to a large extent structured by physical infrastructure, legislation and institutions developed during the colonial period, and by import-substitution policies which during the first decades after independence to a large extent allowed the transport system to deteriorate. However, since the late 1980s the structural adjustment policies have led to a renewed interest both from the government and the donors in developing the transport infrastructure. At the same time trade liberalisation, deregulation of domestic trade and privatisation of the parastatals have since the mid-1990s led to a reshaping of both trade and transport which is still ongoing. The so-called logistical revolution, which since the early 1970s has revolutionised transport in the industrialised and industrialising world, has with a delay of two decades also reached Africa. This is resulting in much closer integration of transport into production and trade which tend to shift the focus away from the physical transport infrastructure to the institutional structures and organisations which support and exploit the infrastructures. This paper tries to describe the resulting transformation of the Kenyan transport system.
Keywords: 330; Güterverkehr; Branchenentwicklung; Kenia